Vancomycin-resistant Enterococcus faecium: A current perspective on resilience, adaptation, and the urgent need for novel strategies - Ana C. Almeida-Santos; Carla Novais; Luísa Peixe; Ana R. Freitas (Journal of Global Antimicrobial Resistance)
Vancomycin-resistant Enterococcus faecium (VREfm) has become a critical opportunistic pathogen, urgently requiring new antimicrobial strategies due to its rising prevalence and significant impact on patient safety and healthcare costs. VREfm continues to evolve through mutations and the acquisition of new genes via horizontal gene transfer, contributing to resistance against several last-resort antibiotics. Although primarily hospital-associated, VREfm are also detected in the community, food chain, livestock, and environmental sources like wastewater, indicating diverse transmission pathways and the need for a One Health approach. Advances in genomics have shed light on VREfm's persistence in hospital settings, particularly its adaptation to the gastrointestinal tract of hospitalized patients, recent clonal shifts, and the dominance of specific clonal lineages. Despite extensive research, significant gaps remain in understanding the molecular mechanisms behind VREfm's unique adaptation to clinical environments. In this review, we aim to present an overview of VREfm current prevalence, mechanisms of resistance, and unveil the adaptive traits that have facilitated VREfm's rise and global success. A particular focus is given to key plasmids, namely linear plasmids, virulence factors, and bacteriocins as potential drivers in the global emergence of the ST78 clonal lineage. We also address diagnostic challenges and the limited treatment options available for VREfm, as well as emerging antibiotic alternatives aimed at restoring gut microbiota balance and curbing VREfm proliferation. A multifaceted approach combining research, clinical practices, and public health policies is crucial to mitigate the impact of this superbug and preserve antimicrobial effectiveness for future generations.